O inadmissível roubo da carta de alforria do nagô Pedro Allgayer: a escravidão em uma zona de imigração alemã (RS, séc. XIX) - Paulo Roberto Staudt Moreira; Miquéias Henrique Mugge (Ciências Sociais Unisinos)
Little is known about the formation of slavery in regions of European immigration in Brazil. Relatively recently, historiography committed with identities grounded in local and Germanic family ancestries denied the historical black presence in these areas. Such discourse argued that German immigrants were imbued of manual labor and their properties were sustained only by free and familiar manpower. Manipulating documents and sources and seeking theoretical-methodological support in Italian micro-history, we aspire to discuss these precepts in this article. Starting from a trivial case portrayed in a legal document, our goal is to make this case study an efficient observatory that shows the slave society in the German colony of São Leopoldo in the eighteen hundreds.